Evaluation of Supplementation of Bittergourd Fermented Beverage to Diabetic Subjects - C.S. Devaki; K.S. Premavalli (Journal of Pharmacy and Nutrition Sciences, 2014)
Diabetes mellitus is a chronic endocrine diseased condition reflected by higher level of blood glucose which is due to less insulin production, insulin action or both. Bittergourd juice consumption is being traditionally practiced for the treatment of diabetes mellitus in developing country such as India, but not supported through clinical data and highly bitter juice is difficult to drink. Therefore bittergourd fermented beverage with improved nutritional strength and taste was developed and supplemented to diabetic subjects and the evaluation was carried out. The evaluation of the bittergourd fermented beverage, in the first stage was carried out by supplementing the beverage to 30 diabetic subjects as an early morning drink in fasting conditionand the control group was asked to drink water. The fasting and post prandial blood sugar levels were studied and diabetic symptoms were noted. The impact of supplementation of bittergourd fermented beverage on diabetic subjects showed that subjects had significant improvement in reducing the symptoms of diabetes, as well reduced the fasting and post prandial glucose levels by 31% and 25% respectively when compared with the control group. Further 16 diabetic subjects who expressed their consent were given the bittergourd fermented beverage for a period of 5 months and the results of the long duration supplementaion indicated that there was a reduction of fasting blood glucose by 43% and post prandial blood glucose by 41% reflecting advantage of continued consumption of the beverage. In order to understand the direct action of the beverage on blood lipid profile–serum cholesterol, triglycerides, low density lipoprotein cholesterol, high density lipoprotein cholesterol as measured before and after supplementation showed the changes by 4-7% which is not considerable. However the glycoslated haemoglobin indicated encouraging results after the supplementation showing good control from fair control. Therefore, the study clearly reflected the positive effect of bittergourd fermented beverage in reducing and controlling blood sugar levels.